Study of Groundwater Salinity Distribution in Coastal Areas, Adimulyo Sub-district, Kebumen Regency, Central Java - Winarno; Agung Adiputra (Pendidikan Geografi Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
Groundwater salinization occurs in Adimulyo Sub-district, Kebumen Regency due to human activities. A very slow river flow, due to its small hydraulic gradient towards the estuary area. Reduced groundwater due to increased uptake by human activities causes intrusive river water which results in brackish groundwater. The data analysis carried out in the study was based on the primary data of the sample whose groundwater salinity was measured, showing the influence of the salt solution at a certain level which indicates a level of salinity with a negative chloride ion content. The salinity value belongs to the type of brackish water. Electrical Conductivity Groundwater shows the nature of conducting electricity from water. The highest groundwater salinity is in the area of Adimulyo Sub-district, Kebumen Regency, the middle part, which ranges from 4.45